Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924 - Frank, David (Labour / Le Travail, 2001)
The article reviews the book, "Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924," by John H. M. Laslett.